Internalizing Indonesian Values in the Digital Era: A Qualitative Study of Guidance and Counseling Students at an Islamic University - Mega Aria Monica; Uswatun Hasanah (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
Background: Values education is essential for shaping individuals with character and national identity, yet Islamic universities face growing challenges in internalizing Indonesian values amid students' increasing exposure to global influences and digital media. Objective: This study aims to describe the forms and practices of internalizing Indonesian values among BKPI students at UIN Raden Intan Lampung, identify supporting and inhibiting factors, and formulate strengthening strategies, guided by three research questions: (1) How are Indonesian values internalized? (2) What are the supporting and inhibiting factors? (3) What strategies can strengthen values education? Method: A descriptive qualitative approach was employed with 10 purposively selected BKPI students (semesters 5 and 7) and 2 academic advisors. Data were collected over four months through semi-structured interviews, participatory observation, and documentation, analyzed using Miles and Huberman's interactive model, with trustworthiness ensured through triangulation and member checking. Results: Internalization occurs through academic, social, and religious activities across five value dimensions: religiosity (9/10), humanity (8/10), unity (8/10), democracy (7/10), and social justice (7/10). Supporting factors include lecturers' role modeling, inclusive campus culture, and value-oriented activities, while inhibiting factors comprise social media influence (6/10), lack of structured reflection, and suboptimal curriculum integration. Three strategies were formulated: curriculum integration, digital media optimization, and sustainable mentoring. Conclusion: The findings align with Bandura's social learning theory and support Bronfenbrenner's ecological systems theory. Limitations include single-institution focus and small sample size (n=10), limiting generalizability. This research contributes conceptually to values education in Islamic higher education, reinforcing BKPI students' roles as agents of religious, nationalist, and humanistic values.